Activatable polymer nanoagonist for second near-infrared photothermal immunotherapy of cancer - Yuyan Jiang (Nature Portfolio, 2021)
Precise control of immune response remains challenging for cancer immunotherapy. Here, the authors report on photothermally activatable semiconducting polymeric pro-agonist in response to second near-infrared window light for regulated photothermal immunotherapy.